Beyond the Basics: Assessing the Dimensions of Health Center Services in East Idi Sub-district, East Aceh District - Nazaruddin, Nazaruddin; Herdiana, Dian; Shafarina, Shafarina; Murniati, Murniati; Alfiady, Teuku; Alwi, Alwi (International Journal of Public Administration Studies, 2023)
This study endeavors to assess the Quality of Health Center Services in East Idi District, East Aceh Regency, with a specific focus on the sub-district of East Idi. Utilizing a descriptive qualitative analysis, primary and secondary data were collected through observation, interviews, and documentation. The study employed data reduction, presentation, and conclusion as analytical techniques. Findings revealed shortcomings in the physical evidence aspect (Tangibles) of the UPTD Puskesmas Idi Timur, East Aceh Regency, concerning inadequate facilities and infrastructure. The reliability of the health center service process was deemed unsatisfactory due to undisciplined and unprofessional staff. However, responsiveness scored well, with puskesmas staff demonstrating alertness and receptiveness to community inquiries. Guarantees, ensuring convenience in obtaining health services, were positively acknowledged. Employees' empathy received favorable assessments, showcasing a friendly demeanor and openness to public feedback.Despite these positive aspects, the study reiterated concerns about the unreliability of health center staff, emphasizing the need for discipline and professionalism. While responsiveness and guarantees were praised, continuous efforts are required for sustained improvement. The overall emphasis is on enhancing the quality of health services by addressing the identified areas of deficiency and promoting a culture of professionalism and empathy among health center personnel.